Scientific monitoring, development of rapid diagnostic techniques or increase in public infrastructure? How to effectively deal with ancient viruses under glaciers as the climate warms up - Yu Gu (Sustainable Futures, 2025)
In recent years, scientists have discovered ancient viruses beneath glaciers. As the climate continues to warm, these ancient viruses are gradually released, posing a threat to global public health. The common response strategies to ancient viruses include scientific research monitoring, developing rapid diagnostic techniques, and expanding public infrastructure. To determine the appropriate scope for each of these response strategies, this article constructs three differential game models and compares and analyses the equilibrium results derived from the models. The study finds that when the benefit gained per unit of ancient virus addressed is low, the strategy of developing rapid diagnostic technologies yields the greatest societal benefit for governments. Conversely, when the benefit gained per unit of ancient virus addressed is high, the strategy of expanding public infrastructure enables governments to achieve the greatest societal benefits. If the costs of addressing ancient viruses and the benefits derived are high, then societal forces can obtain the greatest societal benefit under the scientific research monitoring strategy. Otherwise, societal forces can achieve the greatest societal benefit with the strategy of developing rapid diagnostic technologies.